Pengaruh Partisipasi Masyarakat terhadap Keberhasilan Program Bank Sampah: Studi pada Bank Sampah Sehati - Rafi Kurniansyah; Lala M. Kolopaking (Jurnal Ilmu Sosial dan Humaniora, 2026)
Community participation plays an important role in determining the success of community-based waste management programs, especially waste banks. This study aims to analyze how different forms of community participation influence the success of the Sehati Waste Bank. Participation is examined through four dimensions: planning, implementation, utilization of results, and evaluation. This research employs a quantitative approach using a survey method involving 64 respondents. The findings show that community participation has a significant influence on the success of the waste bank. However, participation that is directly related to perceived benefits plays a more dominant role compared to other forms of participation. These findings indicate that the success of community-based programs is strongly influenced by how far the community can directly experience and utilize the benefits of the program.